A monograph of the birdwing butterflies : the systematics of Ornithoptera, Troides and related genera - Haugum, J. (Scandinavian Science Press, 1978)
Vol. 1: The genus Ornithoptera. - -Vol. 2: The general Trogonoptera, Ripponia and Troides.